Electronic structure and magnetism of 3d-transition metal pnictides (Springer, 2009)
This book presents the results of investigations into the magnetic properties of 3d-transition metal compounds. In particular, it deals with 3d-metal pnictides (i.e., compounds containing phosphorus, arsenic, antimony or bismuth). Part I reports the experimental data together with phenomenological discussions from fundamental and application view points. Part II addresses how some of interesting behaviors mentioned in Part I can be explained on the basis of an itinerant electron picture. Band structures obtained by first-principle calculations are applied to introduce theories to calculate various properties such as susceptibility, magnetic ordering, and magnetic transitions, etc.